Steel for drill collar

The optimized drill collar steel alloy addresses SSC issues in acidic environments by balancing composition to achieve robust mechanical properties and exceptional SSC resistance, ensuring extended service life and reduced costs.

CN119685725AActive Publication Date: 2025-03-25XIANGFAN JINNAITE MACHINERY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411843727.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-14
Publication Date
2025-03-25
Estimated Expiration
2044-12-14

AI Technical Summary

Technical Problem

Existing drill collars in acidic oil and gas fields suffer from short service life due to sulfide stress cracking (SSC) caused by high H2S concentrations, leading to frequent failures and high drilling costs.

Method used

A drill collar steel alloy with optimized composition (C: 0.01-0.06%, Mn: 20.3-21.7%, Cr: 18.0-20.0%, Mo: 0.5-3.5%, Ni: 1.4-4.5%, N: 0.6-2.2%, W: 0.43-0.75%, B: 0.006-0.012%) that balances mechanical properties with exceptional SSC resistance, achieved through careful control of W and B content to maintain stability and reliability in acidic environments.

Benefits of technology

The alloy exhibits superior SSC resistance, extending service life and reducing drilling costs by preventing cracking and failure under high H2S conditions, while maintaining mechanical performance comparable to or exceeding traditional drill collar steels.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to steel for a drill collar, which comprises the following components in percentage by mass: 0.01 to 0.06 percent of C, 20.3 to 21.7 percent of Mn, 18.0 to 20.0 percent of Cr, 0.5 to 3.5 percent of Mo, 1.4 to 4.5 percent of Ni, 0.6 to 2.2 percent of N, 0.43 to 0.75 percent of W, 0.006 to 0.012 percent of B and the balance of Fe and inevitable impurities, W and B meet the condition that ([W] / 183.8) / ([B] / 10.8) = 3.17 to 6.23, and in the formula, [W] and [B] respectively represent the mass percentage contents of W and B in the steel.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a drill collar steel, which not only has mechanical properties equal to or higher than those of conventional drill collar steels, but also has excellent SSC resistance properties and is particularly suitable for use in the drilling process of acidic oil and gas fields. Background Art

[0002] The drill collar is the main component of the drill string. During the oil and gas drilling process, positioning is usually carried out by a magnetic compass or magnetic instrument. In order to avoid interference with positioning, a non-ferromagnetic drill collar is required. At the same time, in order to provide drilling pressure to the drill bit and improve the rigidity of the drill string, the drill collar needs to have excellent strength and toughness characteristics. The drilling process often faces electrochemical corrosion, pitting corrosion, etc., requiring the drill collar material to have excellent corrosion resistance. In summary, the existing drill collar materials have more stringent requirements on various characteristics, resulting in a relatively high cost. Therefore, it is expected that the drill collar material can serve as long as possible.

[0003] However, during the drilling process in sour oil and gas fields, the working environment is accompanied by high concentrations of H2S. Working for a long time under high H2S will cause sulfide stress cracking (SSC) in the drill collar, which often causes cracking and fracture failure of the drill collar, resulting in a short service life and high drilling costs.

[0004] Based on the above problems, the inventors of the present invention hope to provide a drill collar material that can effectively resist sulfide stress cracking, extend its stable and reliable service time during drilling and production in acidic oil and gas fields, and reduce drilling and production costs. Summary of the invention

[0005] The present invention provides a drill collar steel, which not only has mechanical properties equal to or higher than those of conventional drill collar steels, but also has excellent SSC resistance. When used in the drilling process of acidic oil and gas fields, the drill collar steel is not prone to cracking or breaking, has stable working performance and reliable service time, and can effectively reduce drilling costs.

[0006] The technical objectives of the present invention are achieved by the following means.

[0007] The object of the present invention is to provide a steel for drill collars, the composition of which is calculated by mass percentage: C: 0.01-0.06%, Mn: 20.3-21.7%, Cr: 18.0-20.0%, Mo: 0.5%-3.5%, Ni: 1.4-4.5%, N: 0.6-2.2%, W: 0.43-0.75%, B: 0.006-0.012%, the balance is Fe and unavoidable impurities, and W and B satisfy ([W] / 183.8) / ([B] / 10.8)=3.17-6.23, wherein [W] and [B] represent the mass percentages of W and B in the steel, respectively.

[0008] Next, the composition design principle of the present invention is introduced.

[0009] C: Carbon is one of the most important austenite-forming elements. The present invention aims to obtain a fully austenitic structure to ensure the paramagnetism of the material, so a certain carbon content is required. Moreover, the addition of carbon helps to improve the strength of the steel, which is also very important for ensuring the strength characteristics of the steel. However, too high a carbon content is prone to form carbides, resulting in a decrease in the corrosion resistance of the steel. Therefore, taking into account the metallographic structure, strength, and corrosion resistance of the present invention, the present invention sets the carbon content in the steel to 0.01-0.06%.

[0010] Mn: In the present invention, manganese is a crucial element, which is conducive to ensuring the strength of the steel and stabilizing the austenite structure. At the same time, only a sufficiently high manganese content can ensure that a sufficient amount of nitrogen is dissolved in the steel, thereby ensuring that the steel has a sufficiently high nitrogen content to replace nickel with nitrogen and reduce the cost of the steel. However, too high a manganese content will lead to deterioration of the corrosion resistance of the steel. Taking into account the metallographic structure, strength, and corrosion resistance of the present invention, the present invention sets the manganese content in the steel to 20.3-21.7%.

[0011] Cr: On the one hand, chromium can stabilize the austenite structure of steel. On the other hand, the most important role of chromium is to ensure that the steel has sufficient corrosion resistance. However, too high chromium content will lead to a decrease in the processing performance of the steel and a deterioration in toughness. Taking into account the metallographic structure, corrosion resistance, processing performance, toughness and other characteristics of the present invention, the present invention sets the chromium content in the steel to 18.0-20.0%.

[0012] Mo: Molybdenum is an important element to ensure that the steel has excellent corrosion resistance. Molybdenum is also an element that greatly improves strength. However, too high a molybdenum content will deteriorate the processing performance of the steel. Taking into account the corrosion resistance and processing performance of the present invention, the molybdenum content in the steel is set to 0.5%-3.5%.

[0013] Ni: Nickel is an important element for improving the corrosion resistance of steel and is important for maintaining the stability of austenite. However, the shortage of nickel resources is becoming increasingly serious and the price of nickel remains high. Therefore, the present invention uses high manganese and high nitrogen to replace nickel. Based on corrosion resistance considerations and cost control, the present invention sets the nickel content in the steel to 1.4-4.5%.

[0014] N: The addition of nitrogen can maintain the stability of austenite, and is an element that improves strength and ensures corrosion resistance. By increasing the amount of manganese added, the solubility of nitrogen in the steel matrix can be increased, thereby replacing most of the nickel element with manganese and nitrogen. However, too high a nitrogen content will make it difficult to add and easily form pores in the steel matrix, affecting the various properties of the steel. Based on the needs of metallographic structure, strength and corrosion resistance, the present invention sets the nitrogen content in the steel to 0.6-2.2%.

[0015] W: Tungsten is an element that stabilizes the formation of austenite. The austenite matrix can ensure that the steel has paramagnetism and can effectively improve the strength and corrosion resistance of the steel. However, too high a content will increase the cost and deteriorate the plasticity of the steel. Taking into account the structure, non-magnetism, strength, corrosion resistance and plasticity of the steel, the present invention sets the tungsten content in the steel to 0.43-0.75%.

[0016] B: Boron is an element that improves hardenability and promotes the formation of austenite. It can ensure non-magneticity and greatly improve the strength of steel, but too high a content will lead to deterioration of the plasticity and processing performance of the steel. Taking into account the structure, strength and plasticity of the steel of the present invention, the boron content in the steel of the present invention is set to 0.006-0.012%.

[0017] Values ​​of ([W] / 183.8) and ([B] / 10.8): As described in the previous background technology, existing drill collar materials are easily affected by H2S and crack or even break when working in acidic oil and gas fields, resulting in a short effective service life of the drill collar, poor working stability, and high drilling and production costs. The inventors of the present invention have found through repeated experiments that by synergistically controlling the content of W and B, the SSC resistance of the steel can be effectively improved, so that when working in acidic oil and gas fields, sulfide stress cracking will not occur due to high concentrations of H2S, thereby ensuring that the drill collar has an excellent service life and extending the time of reliable and stable operation, thereby effectively reducing drilling and production costs. After confirmation by the inventors of the present invention, the W and B content range that can ensure that the steel has excellent SSC resistance is defined as ([W] / 183.8) / ([B] / 10.8)=3.17-6.23.

[0018] In the present invention, the unavoidable impurity elements may be P, S, O, H, etc. These elements are common elements in steel, introduced through raw materials and cannot be completely removed. The lower the content of the impurity elements is controlled, the better the performance of the corresponding steel is, but the higher the preparation cost of the steel is. Considering the performance and cost comprehensively, the P and S of the present invention are controlled below 0.01%, and the O and H are not higher than 50ppm.

[0019] As a non-limiting description, the drill collar steel of the present invention has a yield strength of more than 980 MPa, a tensile strength of more than 1055 MPa, an elongation of not less than 20%, a cross-sectional shrinkage of not less than 50%, an impact energy at room temperature of not less than 90 J, and a relative magnetic permeability μ r ≤1.005.

[0020] The drill collar steel of the present invention has excellent SSC resistance. According to method A in NACE TM0177-2016, the drill collar steel sample (φ6.35mm×25.4mm) of the present invention is immersed in a test liquid, the test liquid is: acetic acid + sodium acetate is added to a 5wt.% NaCl aqueous solution to adjust the pH of the test liquid to 3.5, the liquid temperature is 25°C, the atmosphere is CO2: 0.95atm, H2S: 0.05atm, 90% of the yield strength is loaded as the load stress, and there is no crack after immersion in the immersion liquid for 720 hours.

[0021] As another aspect of the present invention, the present invention also provides the application of the aforementioned drill collar steel in drilling and production of acidic oil and gas fields. Since the drill collar steel of the present invention not only has the excellent mechanical properties of traditional drill collar steel, it also has excellent anti-SSC properties and can effectively resist stress cracking caused by H2S under high humidity and high H2S concentration conditions. Therefore, the drill collar steel of the present invention is particularly suitable for drilling and production of acidic oil and gas fields.

[0022] As a non-limiting description, the method for preparing the drill collar steel of the present invention can be prepared by traditional smelting and casting, or by using an electroslag remelting process.

[0023] As a non-limiting description, after the ingot is prepared, the drill collar steel of the present invention preferably includes a primary hot working step, and the hot working can be rough rolling, forging and blanking, etc., and the corresponding size is obtained through the primary hot working. Before the primary hot working, it preferably includes a homogenization treatment step, the homogenization temperature is 1150-1250°C, the time is 2-5h, and the primary hot working is directly carried out after the homogenization treatment.

[0024] As a non-limiting description, after the above-mentioned primary hot working, it is preferably subjected to a solution treatment at 1000-1150° C., and the time of the solution treatment is set to 2-4 hours.

[0025] As a non-limiting description, after the above-mentioned solution treatment, secondary hot working strengthening is preferably carried out, and the secondary hot working strengthening can be, for example, finishing rolling with a total reduction rate of 15-65% at 500-800°C, or extrusion or forging with a total cross-sectional reduction rate of 10-70% at 500-800°C.

[0026] The beneficial effects of the present invention are as follows.

[0027] The present invention obtains drill collar steel with excellent strength, toughness and plasticity through the adjustment and optimization of the composition. Its various mechanical properties reach or exceed the corresponding mechanical property level of traditional drill collar steel, and can meet the requirements of various mechanical properties of drill collars in the drilling process. The steel obtains the matrix structure of austenite through the control of the composition, belongs to non-magnetic material, and has a relative magnetic permeability μ r ≤1.005, and will not interfere with exploration instruments during the drilling process; in particular, by adding W and B and synergistically controlling the contents of the two, the drill collar steel finally obtained by the present invention has excellent resistance to sulfide stress cracking, and will not have cracking failure problems even when working for a long time under high concentration H2S conditions. It has an excellent service life and stable long-term working ability, which makes the steel of the present invention particularly suitable for use in drilling and production of acidic oil and gas fields, and can significantly reduce drilling and production costs. DETAILED DESCRIPTION

[0028] In order to enable ordinary technicians in the field to fully understand the technical solutions and beneficial effects of the present invention, further explanation is given below in conjunction with specific test examples.

[0029] The molten steel was melted according to the designed composition and cast into ingots, the contents of P and S were controlled at 0.008±0.001%, the contents of O and H were controlled at 40ppm±5ppm, and the size of the ingot was 1000mm long × 400mm wide × 400mm high. The specific composition is shown in Table 1, where k=([W] / 183.8) / ([B] / 10.8). Test numbers 1, 2, and 3 cast two ingots of the above sizes, which were named test numbers 1-1, 1-2, 2-1, 2-2, 3-1, and 3-2, respectively.

[0030] Test numbers 1-2, 2-2, and 3-2 were finished in the ingot state, and the remaining sample numbers were homogenized at 1180°C for 3 hours, then hot forged into round bars with a diameter of 300 mm, and then solution treated at 1080°C for 2.5 hours, air cooled to 675°C, and extruded to achieve a cross-sectional reduction of 50% to obtain finished bars.

[0031] The finished rod products were tested for various properties. The tests of yield strength, tensile strength, elongation and cross-sectional reduction were carried out in accordance with GB / T228.1-2021, the impact energy test was carried out in accordance with GB / T229-2020, and the relative magnetic permeability test was carried out in accordance with GB / T 35690-2017. The anti-SSC properties were tested according to method A in NACE TM0177-2016. The specimen (φ6.35mm×25.4mm) was immersed in the test liquid. The test liquid was: acetic acid + sodium acetate was added to a 5wt.% NaCl aqueous solution and the pH of the test liquid was adjusted to 3.5. The liquid temperature was 25°C, and the atmosphere was CO2: 0.95atm, H2S: 0.05atm. 90% of the yield strength (the yield strength obtained by sampling and testing on the same rod) was loaded as the load stress. After immersion in the immersion liquid for 720 hours, the presence of cracks was observed.

[0032] Table 1: Composition of various steel materials, %, the remainder is Fe.

[0033]

[0034] The results of various tests on the above-mentioned test numbers 1 to 12 steels are shown in Table 2.

[0035] Table 2: Properties of various steels.

[0036]

[0037] The above-mentioned inventive examples and comparative examples are further analyzed and explained below in conjunction with Tables 1 and 2.

[0038] The test numbers 1 to 6 in Table 1 all meet the composition requirements of the present invention, and therefore, the test numbers 1 to 6 are inventive examples of the present invention. It is not difficult to find from the test results that the steels with the composition of test numbers 1 to 6 meet the requirements of the present invention in terms of yield strength, tensile strength, elongation, cross-sectional reduction, impact energy, and relative magnetic permeability. In particular, there are no cracks after testing according to the requirements of NACE TM0177-2016, proving that the steels with the composition of the present invention have excellent SSC resistance.

[0039] In Table 2, test numbers 1-2, 2-2, and 3-2 are all performances tested under cast conditions, while test numbers 1-1, 2-1, and 3-1 with the same composition are samples after strengthening deformation. It is not difficult to see that their yield strength and tensile strength have increased, while elongation, cross-sectional shrinkage, and toughness have decreased to a certain extent, but they are still within the scope required by the present invention. The experiment confirmed that the steel with the composition of the present invention, whether in cast or strengthened deformation, can meet the various performance requirements of the present invention, but the performance focus is on the conversion between strength and plastic toughness. The user can actually choose the cast state or strengthened deformation state based on the performance requirements.

[0040] Test numbers 7, 8, 9, and 10 respectively adjusted the W and B element contents of test numbers 1, 2, 3, and 4. Although the adjusted W and B contents still meet the requirements of the present invention, the k [([W] / 183.8) / ([B] / 10.8)] value is not within the scope of the invention. The test results show that although the strength, plasticity, toughness, and magnetic properties of test numbers 7, 8, 9, and 10 meet the requirements of the present invention, cracks appear after testing according to the requirements of NACE TM0177-2016, which proves that the above-mentioned steels have poor SSC resistance and cannot meet the requirements of long-term stable operation in sour oil and gas field conditions.

[0041] Test numbers 11 and 12 omitted B and W on the basis of test numbers 5 and 6, respectively. The results showed that their yield strength and tensile strength decreased and could not meet the requirements of the present invention of a yield strength of more than 980 MPa and a tensile strength of more than 1055 MPa. In addition, due to the lack of B or W, the synergistic effect of W and B could not be exerted. Finally, after testing, their anti-SSC properties were poor and could not meet the requirements of the present invention.

[0042] It is not difficult to see from the above invention examples and comparative examples that by synergistically adding W and B and controlling the content relationship of W and B within the corresponding range, a drill collar steel having strength, plasticity, toughness and relative magnetic permeability that meet the requirements can be finally obtained. Most importantly, the steel has excellent anti-SSC properties, can be suitable for the requirements of long-term stable operation under acidic oil and gas field working conditions, has an excellent service life, and can effectively control drilling and production costs.

[0043] The above embodiments are only used to help understand the method and core idea of ​​the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.

[0044] The above description of the disclosed embodiments enables those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but will conform to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A drill collar steel, characterized in that: The composition of the drill collar steel is calculated by mass percentage as follows: C: 0.01-0.06%, Mn: 20.3-21.7%, Cr: 18.0-20.0%, Mo: 0.5%-3.5%, Ni: 1.4-4.5%, N: 0.6-2.2%, W: 0.43-0.75%, B: 0.006-0.012%, the remainder is Fe and unavoidable impurities, and W and B satisfy ([W] / 183.8) / ([B] / 10.8)=3.17-6.23, wherein [W] and [B] represent the mass percentages of W and B in the steel, respectively.

2. The drill collar steel according to claim 1, characterized in that: The yield strength of the drill collar steel is above 980 MPa.

3. The drill collar steel according to any one of claims 1 to 2, characterized in that: The tensile strength of the drill collar steel is above 1055 MPa.

4. The drill collar steel according to any one of claims 1 to 3, characterized in that: The elongation of the drill collar steel is not less than 20%.

5. The drill collar steel according to any one of claims 1 to 4, characterized in that: The cross-sectional shrinkage of the drill collar steel is not less than 50%.

6. The drill collar steel according to any one of claims 1 to 5, characterized in that: The room temperature impact energy of the drill collar steel is not less than 90J.

7. The drill collar steel according to any one of claims 1 to 6, characterized in that: The relative magnetic permeability μ of the drill collar steel r ≤1.

005.

8. The drill collar steel according to any one of claims 1 to 7, characterized in that: The drill collar steel has excellent SSC resistance.

9. The use of the drill collar steel according to any one of claims 1 to 8, characterized in that: The drill collar steel is used for drilling in acidic oil and gas fields.

Citation Information

Patent Citations

  • High-strength nonmagnetic stainless steel, component containing the same and manufacturing method thereof

    CN101298649A

  • Low-nickel austenitic stainless steel and use of the steel

    CN102985579A

  • High strength non-magnetic stainless steel and method for producing the same

    EP0987342A1

  • Austenitic stainless steel and drill collar

    US4502886A